2013
DOI: 10.1186/1471-230x-13-60
|View full text |Cite
|
Sign up to set email alerts
|

Transarterial chemoembolization for hepatocellular carcinoma with portal vein tumor thrombus: a meta-analysis

Abstract: BackgroundAlthough transarterial chemoembolization (TACE) has been used extensively for advanced hepatocellular carcinoma (HCC) with portal vein tumor thrombus (PVTT), no consensus has been reached and an evidence base for practice is lacking. This meta-analysis evaluated the efficacy and safety of TACE for treatment of HCC with PVTT.MethodsOvid Medline, EMBASE, Web of Knowledge, and Cochrane library databases were searched up to August 2012 for controlled trials assessing TACE in patients with PVTT. Data conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
109
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 141 publications
(118 citation statements)
references
References 18 publications
2
109
1
6
Order By: Relevance
“…Расширение показаний для хирургического лечения ГЦР нуждается в активном изучении [28,29,30]. В некоторых неоперабельных случаях ГЦР может быть эффективной хемоэмболизацией [31,32]. Стадия С первоначально выделена на группе лишь из 102 пациентов [33].…”
Section: обзор исторического развития шкал и классификаций при гцкunclassified
“…Расширение показаний для хирургического лечения ГЦР нуждается в активном изучении [28,29,30]. В некоторых неоперабельных случаях ГЦР может быть эффективной хемоэмболизацией [31,32]. Стадия С первоначально выделена на группе лишь из 102 пациентов [33].…”
Section: обзор исторического развития шкал и классификаций при гцкunclassified
“…In both the Asian Pacific Association for the Study of the Liver (APASL) guidelines and HKLC scoring system, TACE is a possible treatment option for patients with HCC and limited portal vein thrombosis [8,10] ( Figure 6). A number of Asian studies and a meta-analysis of eight trials (including five retrospective studies) have shown a survival benefit vs untreated control arms, on condition that the portal vein thrombosis is limited [37][38][39][40] . However, it is not possible to validate the use of TACE in this indication on the basis of these results.…”
Section: Recommendations For the Use Of Chemoembolization In Patientsmentioning
confidence: 99%
“…Hepatitis B and C and alcohol abuse are major risk factors for HCC. Although local ablation techniques and multikinase inhibitors, such as radiofrequency ablation and sorafenib, are increasingly prevalent, transcatheter arterial chemoembolization (TACE) remains one of the standard treatments for patients with intermediate-and advanced-stage HCC (1)(2)(3). Several randomized controlled studies have revealed that TACE improves survival and controls the symptoms of HCC (4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%